EVALUASI MANAJEMEN RISIKO KANTOR AKUNTAN PUBLIK (KAP) DALAM KEPUTUSAN PENERIMAAN KLIEN BERDASARKAN PERTIMBANGAN DARI RISIKO KLIEN, RISIKO AUDIT DAN RISIKO BISNIS KAP - Sensi, Ludovicus (UI Scholars Hub, 2006)
The objective of this research is to understand the risk management factors which should be performed by the accountingfrm in the process ofclient acceptance decision by considering of three risks factors: Client Risk, Audit Risk and Auditor s Business Risk. The client risk was determined by management integrity valuation and client’s business risk, meanwhile, the audit risk was determined by the nature of the audit engagement, related parties transactions, client’s prior knowledge and ex periences, and also from the deep understanding of auditors in regards to the error andfraud which is possible performed by the client. Furthermore, auditor s business risk was determined by considering whether the client s profiles is a public company, regulated industry or high profile company. In order to enhance this research, this paper also discusses how the auditfee and the role of specialist will impact to client s acceptance decision. In conducting the model testing, this research was performed through a field of empirical testing in one of the accounting firm ( archival data).